The More Business Owners the Merrier? The Role of Tertiary Education - Mirjam van Praag; Andre van Stel (Tinbergen Institute, 2011)
Policy in developed countries is often based on the assumption that higher business ownership rates induce economic value. Recent microeconomic empirical evidence casts doubts on the validity of this assumption or, at least, leads to a more nuanced view: Especially the top performing business owners are responsible for the value creation of business owners. Other labor market participants would contribute more to economic value creation as an employee than a business owner. The implied existence of an 'optimal' business ownership rate would thus replace the dictum of 'the more business owners, the merrier'. We attempt to establish whether there is such an optimal level, while investigating the role of tertiary education. Two findings stand out. First, by estimating extended versions of traditional Cobb Douglas production functions on a sample of 19 OECD countries over the period 1981-2006, we find indeed robust evidence of an optimal business ownership rate (at around 12.5%, on average). Second, the relation between business ownership and macroeconomic productivity is steeper for countries with higher participation rates in tertiary education. Thus, the optimal business ownership rate tends to decrease with tertiary education levels. This is consistent with microeconomic theory and evidence showing that entrepreneurs with superior levels of human capital run larger firms.
Keywords: E23; J24; L26; O40; O57; 330; entrepreneurship; business ownership; human capital; (returns to) education; cross-country comparison; production function